2007
DOI: 10.1097/01.cej.0000236255.95769.22
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption and gastric cancer by location and histological type: case–control and meta-analysis

Abstract: The available information favours a greater impact of environmental exposures on intestinal type gastric cancer, and risk factors for the cardia and distal stomach cancers also appear to be different. We aimed to estimate the association between fruit and vegetable intake and gastric cancer, by location and histological type. We performed a population-based case-control study and a meta-analysis of studies addressing this issue. Incident cases (n=305) were identified in two large teaching hospitals (Porto, Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 60 publications
5
133
0
5
Order By: Relevance
“…A meta-analysis showed for fruits a relative risk of 0.6 (95 % CI, 0.4-0.8) when comparing the highest to the lowest category of consumption. For vegetables, it was 0.6 (95 % CI, 0.5-0.8) [28]. The protective effect of fruits and vegetables can explain that, in contrast to esophageal adenocarcinoma where obesity and tobacco consumption play a major role, incidence rates did not increase for cardia cancer.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A meta-analysis showed for fruits a relative risk of 0.6 (95 % CI, 0.4-0.8) when comparing the highest to the lowest category of consumption. For vegetables, it was 0.6 (95 % CI, 0.5-0.8) [28]. The protective effect of fruits and vegetables can explain that, in contrast to esophageal adenocarcinoma where obesity and tobacco consumption play a major role, incidence rates did not increase for cardia cancer.…”
Section: Discussionmentioning
confidence: 91%
“…The protective role of vegetables and fresh fruits reported in case-control studies and not in cohort studies could be attributed to a period effect [27]. In the meta-analysis of case-control studies the relative risk for non-cardia gastric cancer was 0.61 (0.44-0.84) when comparing the highest to the lowest category of fruit consumption and 0.75 (0.59-0.95) when comparing the highest to the lowest category of vegetable consumption [28].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, fruit intake (notably citrus fruits) was associated with a significant reduction in GCA risk, with the exception of the lowest quartile of consumption. Lunet et al [45] reported similar findings in a population-based case-control design and formalized review of the literature through a meta-analysis, concluding that when comparing the highest with the lowest quartile of fruit consumption the relative risk of GCA was 0.53 (95 % CI 0.35-0.80), with similar benefits from vegetable intake (relative risk 0.63, 95 % CI 0.50-0.70). However, other studies have not always confirmed a protective effect from increased vegetable and/or fruit consumption.…”
Section: Dietmentioning
confidence: 53%
“…The positive effect of a diet based on fruits and vegetables has been analyzed in several studies [44,45]. In a meta-analysis by Stevens et al [44], several significant trends were noted.…”
Section: Dietmentioning
confidence: 99%
“…Finally, we included 80 papers for this overview of reviews, but in our article we only reviewed 55 etiological SRs/meta-analyses (Fu et al, 1995;Huang et al, 1998;Jacobs et al, 1998;Danesh et al, 1999;Eslick et al, 1999;Jia et al, 2000;Wu et al, 2000;Xue et al, 2001;Huang et al, 2003;Guo et al, 2004;Li et al, 2004;Botelho et al, 2006;Hu et al, 2006;Jakszyn et al, 2006;Liu et al, 2006;MacLean et al, 2006;Nishino et al, 2006;Tian et al, 2006;Xu et al, 2006;An et al, 2007;Kubo et al, 2007;Lunet et al, 2007;Merrill et al, 2007;Bae et al, 2008;Ladeiras-Lopes et al, 2008;Kuoppala et al, 2008;Shimazu et al, 2008;Zhou et al, 2008;Huang et al, 2009;La Torre et al, 2009;Mulholland et al, 2009;Myung et al, 2009;Yang et al, 2009;Zhang et al, 2009;Cavaleiro-Pinto et al, 2010;Gatto et al, 2010;Hussein et al, 2010;Kang et al, 2010;Kim et al, 2010;…”
Section: Search Resultsmentioning
confidence: 99%